Adoption of ZakaTech in the Time of COVID-19: Cross-Country and Gender Differences - Nashwan, Saeed Awadh; Ismaiel, Abdelhamid Elsayed A.; Muneeza, Aishath; Isa, Mohamad Yazid (Emerald Group Publishing Limited, 2023)
Purpose – Despite the significant growth in Islamic economies and the increasing number of Muslim youths inclining digital services, empirical-based research addressing the adoption of digital Islamic services is still limited. ZakaTech is a new phrase that has recently emerged as a modern term describing novel technologies adopted by zakat institutions; yet, it has been largely neglected in the literature. Therefore, this study aims to provide an integrated model that scrutinizes the determinants of acceptance and use of technology (UTAUT) of ZakaTech, combined with social cognitive theory (SCT), in the midst of the COVID-19 crisis where social distancing is the norm in conducting economic activities. Design/methodology/approach – Based on cross-national evidence from two Muslim-majority countries, a total of 1,006 valid responses were collected from zakat payer users in Saudi Arabia and Egypt using a Web-based survey. To validate the research model and draw significant insights, SmartPLS structural equation modeling was used. Findings – By analyzing both Saudi and Egyptian samples, the authors found that all UTAUT constructs are statistically significant, except for effort expectancy in Egypt. The effects of self-efficacy and social isolation on ZakaTech adoption are supported across both countries. Trust in technology reduces users’ inherent risks and increases their likelihood of adopting ZakaTech services in Saudi Arabia, while this is not the case in Egypt. However, the study revealed that trust in electronic-zakat systems (EZSs) is a vital predictor for mitigating perceived risk among Egyptian users of ZakaTech, but it is not the case in Saudi Arabia. Moreover, significant gender differences were found between males and females in the adoption of such digital services in both countries, particularly regarding self-efficacy, trust in EZSs, social isolation and social influence. Practical implications – The results provide meaningful insights for policymakers to find ways to develop strategies to escalate the adoption of technology in zakat administration and also to create awareness among the users of ZakaTech in a gender-balanced manner that will include zakat payers and recipients as well in the hope that the digital gender divide will be bridged. Bridging the digital gender divide in this regard is imperative for sustainable inclusive development of zakat. Further, strategies need to be developed to provide incentives to zakat authorities and zakat organizations that adopt technology in managing zakat. This is important to escalate the process of fusing technology with zakat, which is an important social finance tool to eradicate poverty in the world